Forestry in India as a Lever for Development - Seth, V. V. (Indian Forester, 1973)
The problems of a rapidly growing population, motivated by the revolution of rising expectations and escalating demands of the populace and industries, pose a challenge to the forestry sector. The role that forestry could play as a lever for development in India has been discussed in this paper against the backdrop of the present situation and trend studies. The population of India will be 750 million in the year 1985, involving addition of 80 million to the working force. The forestry sector could provide employment to 25 million persons (against present estimate of 3 million) and contribute Rs. 25.000 million to GNP (against present estimate of Rs. 5130 million). The forest area is nearly 75 million hectares which contains a growing stock of 2200 million cubic metres. However, the increment from the forests is low. The demand for industrial wood and fuelwood in 1985 would be 50 million cubic metres and 200 million tonnes. Production from the forests will need to be raised substantially. A sound industrial base bas been created but in the interest of its barmonious growth, there Is need for close integration between forestry and industry. This could be achieved by having a separate ministry dealing with these matters. Bold innovations are being made in the field of management and financing of forestry operations. Investments in the forestry sector (for development alone) and forest-based industry sector have been estimated to be Rs. 15,000 million each from now till 1985. Considerable importance is attached to creation of man-made forests, opening up inaccessible forests, augmenting production from commercial forests and minimizing wastage so as to attain self-sufficiency in forest products. A national inventory organization for data collection bas been proposed to be created, and trend studies have been initiated. The forestry sector bolds the key to the future progress and prosperity of the country.